2016
DOI: 10.1158/0008-5472.can-15-1637
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A Is Preferentially Cleaved into Proangiogenic Peptides in the Bone Marrow of Multiple Myeloma Patients

Abstract: Angiogenesis has been postulated to be critical for the pathogenesis of multiple myeloma, a neoplastic disease characterized by abnormal proliferation of malignant plasma cells in the bone marrow (BM). Cleavage of the N-and C-terminal regions of circulating chromogranin A (CgA, CHGA), classically an antiangiogenic protein, can activate latent antiangiogenic and proangiogenic sites, respectively. In this study, we investigated the distribution of CgA-derived polypeptides in multiple myeloma patients and the sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 34 publications
1
41
0
1
Order By: Relevance
“…This dose, administered at 2-3 day intervals, generates peak plasma levels of about 3-4 nM that progressively declines to 0.5-1 nM in 7-8 h and to even lower concentrations at later time points. Considering that circulating levels of CgA in normal subject is 0.2-1 nM (most consisting of fragments lacking the C-terminal region and less than 10-20% consisting of full-length CgA) [25], the biological effects observed in our models are likely patho-physiologically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This dose, administered at 2-3 day intervals, generates peak plasma levels of about 3-4 nM that progressively declines to 0.5-1 nM in 7-8 h and to even lower concentrations at later time points. Considering that circulating levels of CgA in normal subject is 0.2-1 nM (most consisting of fragments lacking the C-terminal region and less than 10-20% consisting of full-length CgA) [25], the biological effects observed in our models are likely patho-physiologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by our observation that anti-PN1 antibodies could neutralize the anti-angiogenic activity of CgA in vitro as well as the anti-tumor activity of CgA in different in vivo models. Moreover, considering that CgA is a good substrate of thrombin and plasmin [24, 25], often present in tumors, and that PN-1 is a potent inhibitor of these proteases [38], it is tempting to speculate that PN-1 may also serve to prevent the local cleavage of CgA in tumors (thereby preserving its anti-angiogenic activity) and/or other factors necessary for tumor progression and invasion. Finally, the bell-shaped dose-response curve and the consequent lack of PN1 induction by high concentrations of CgA may explain the lack of anti-tumor effects with high-dose CgA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structure-function studies have shown that full-length CgA contains a) a latent anti-angiogenic site in the N-terminal region 1-76, b) a latent pro-angiogenic site in the region 352-373 and c) a functional anti-angiogenic site in the C-terminal region 410-439 [14, 16, 17]. The latent anti-angiogenic site is activated by cleavage of the Q 76 -K 77 peptide bond, by unknown enzymes, whereas the pro-angiogenic site can be activated by thrombin- or plasmin-mediated cleavage of the R 373 -R 374 dibasic site [14, 18]. Furthermore, using murine models of mouse mammary adenocarcinomas and melanomas we have shown that full-length CgA and VS-1 can enhance the endothelial barrier function and reduce the trans-endothelial migration of tumor cells, thereby reducing the trafficking of cancer cells from tumor-to-blood and from blood-to-tumor/normal tissues (i.e.…”
Section: Introductionmentioning
confidence: 99%